Pengaruh Kombinasi Dekokta Rimpang Zingiber officinale var rubrum dan Imperata cylindrical Terhadap Kadar CRP Serum Tikus Model Osteoartritis - Dipranastri Widyawati (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2019)
Introduction: Osteoarthritis (OA) is a chronic disorder caused by degenerative process and inflammation that lead to damage on the joint cartilage. Previous research showed that red ginger rhizome (Zingiber officinale var rubrum) and cogon grass rhizome (Imperata Cylindrica) had anti-inflammation and antioxidant effect. This research aimed to know the potencial of the combination of red ginger rhizome (Zingiber officinale var rubrum) and cogon grass rhizome (Imperata Cylindrica) (CRGCG) by measuring the OA rats serum C-Reactive Protein (CRP). C-reactive protein is an acute phase protein used as inflammation marker.Methods: 25 male Wistar rats aged 4 months divided into 5 groups namely positive control group (PC), negative control group (NC), first treatment with dose 9+40 mg/rat/day (T1), second treatment with dose 18+40 mg/rat/day (T2), and third treatment with dose 36+40 mg/rat/day(T3). Rats were induced with Complete Freund’s Adjuvant (CFA) by 0.1 ml/rat on right knee intraarticular of rats to make the OA model. The administration of CRGCG is given for 10 days. The serum CRP level was assessed by CRP ELISA Kit. Data analyzed using Kruskal-Wallis followed by Mann-Whitney test. The result is significant if p<0.05.Result: The CFA induction statistically did not increase the serum CRP level on KP (3,435±0,24) to KN (3,307±0,99) significantly (P>0,05). The administration of CRGCG on the second treatment dose 18+40 mg/rat/day (3±0,2) and third treatment dose 36+40 mg/rat/day able to decrease the serum CRP level significantly (P<0,05).Conclusion: Combination of Red Ginger Rhizome and Cogon Grass Rhizome (CRGCG) dose 18+40 mg/rat/day (T2) and 36+40 mg/rat/day (T3) able to decrease the serum CRP level of OA rats.Keywords: Osteoarthritis, Red Ginger, Cogon Grass, C-Reactive Protein